Source of Inequality in Consumption Expenditure in India: A Regression Based Inequality Decomposition Analysis - Tripathi, Sabyasachi (Journal of Income Distribution®, 2018)
The present paper estimates the Regression based inequality decomposition for the years 2004-05 and 2011-12.The decomposition based regression analysis finds that household size, level of education, share of workers engaged in less productive jobs (such as, casual labour and agricultural worker), regular salary earning member of a household, higher level of land possessed by the households, and households having hired dwelling unit are responsible for the maximum share of inequality in the total inequality of the average monthly per capita expenditure (MPCE) and predicted MPCE in the both urban and rural areas.